A Short and Elegant Synthesis of (±)‐Streptopyrrolidine. (4th April 2013) - Shaameri, Zurina; Ali, Sharifah Hidayah Sharif; Mohamat, Mohd Fazli; Yamin, Bohari M.; Hamzah, Ahmad Sazali
<x xml:space="preserve">Abstract</x> A brief and efficient approach for the synthesis of (±)‐5‐benzyl‐4‐hydroxy‐2‐pyrrolidine (1) from phenylalanine racemate is described. The key step is the stereocontrolled reduction of the keto functionality of benzylated pyrrolidinone intermediate (1) via sodium borohydride in carboxylic acid medium furnishing both (R, R)‐ and (S, S)‐configured diastereomers. The natural (R, R) enantiomer (1), however, crystallized out from its racemic mixture. Structure of 1 was confirmed by NMR, IR, elemental analyzer, and single crystal X‐ray crystallographic techniques.